The Reversal of Empathy-Induced Hypernociception in Male Mice by Intra-Amygdala Administration of Midazolam and Cannabidiol Depends on 5-HT3Receptors - Rodrigues Tavares, Ligia Renata [UNESP]; Baptista-De-Souza, Daniela [UNESP]; Canto-De-Souza, Lucas [UNESP]; Planeta, Cleopatra Da Silva [UNESP]; Guimaraes, Francisco Silveira; Nunes-De-Souza, Ricardo Luiz [UNESP]; Canto-De-Souza, Azair [UNESP] (SAGE Publications, 2023)
Introduction: Empathy is a fundamental prosocial behavior. It has been defined as perception, awareness, and understanding of others' emotional states, including painful processes. Mice living in pairs with conspecific chronic suffering from constriction injury exhibit pain hypersensitivity mediated by the amygdaloid complex. Nevertheless, the underlying mechanisms in the amygdala responsible for this response remain to be determined. This study investigated if the anxiolytic benzodiazepine midazolam (MDZ) and cannabidiol (CBD), a phytocannabinoid with multiple molecular targets, would attenuate this behavioral change. We also investigated if serotonergic and γ-aminobutyric acid (GABA)ergic mechanisms in the amygdala are involved in this effect. Materials and Methods: Male Swiss mice were housed in pairs for 28 days. The pairs were divided into two groups on the 14th day: cagemate nerve constriction and cagemate sham. On the 24th day, cagemates underwent a stereotaxic surgery and, on the 28th day, were evaluated on the writhing test. Results: The results showed that living with chronic pain leads to hypernociception in the cagemate and increases the expression of 5-HT3 receptor (5-HT3R) and glutamic acid decarboxylase 67 within the amygdala. MDZ (3.0 and 30 nmol) and CBD (30 and 60 nmol) attenuated the hypernociceptive behavior. The 5-HT3R antagonist ondansetron (0.3 nmol) prevented the antinociceptive effects of MDZ and CBD. Conclusion: These findings indicate that 5-HT3R and GABAergic mechanisms within the amygdala are involved in the pain hypersensitivity induced by the empathy for pain model. They also suggest that MDZ and CBD could be a new potential therapy to alleviate emotional pain disorders.
Keywords: 5-HT3receptors; cannabidiol; empathy; GABA; mice; nociception